2022
DOI: 10.3847/1538-3881/ac78ed
|View full text |Cite
|
Sign up to set email alerts
|

MOA-2019-BLG-008Lb: A New Microlensing Detection of an Object at the Planet/Brown Dwarf Boundary

Abstract: We report on the observations, analysis and interpretation of the microlensing event MOA-2019-BLG-008. The observed anomaly in the photometric light curve is best described through a binary lens model. In this model, the source did not cross caustics and no finite-source effects were observed. Therefore, the angular Einstein ring radius θ E cannot be measured from the light curve alone. However, the large event duration, t E ∼ 80 days, allows a precise measurement of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 158 publications
0
0
0
Order By: Relevance
“…The downside is that the results are inevitably biased because of the different models assumptions. For example, Bachelet et al (2022b) found a good agreement with the prediction from the Besançon (Robin et al 2003), GalMod (Pasetto et al 2018), Dominik (2006), andKoshimoto et al (2021) models, but small discrepancies exist.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The downside is that the results are inevitably biased because of the different models assumptions. For example, Bachelet et al (2022b) found a good agreement with the prediction from the Besançon (Robin et al 2003), GalMod (Pasetto et al 2018), Dominik (2006), andKoshimoto et al (2021) models, but small discrepancies exist.…”
Section: Introductionmentioning
confidence: 64%
“…These measurements will be based on the lightcurve modeling as well as the modeling of the Roman images near the event location. A double point-spread function fit provides strong constraints on the source and lens magnitudes as well as the relative proper motion μ rel (Bachelet et al 2022a), which is included as the last observable. The typical astrometric precision can be approximated by (Lindegren 1978;Sozzetti 2005), where FWHM is the full width at half-maximum of the optical system and S/N is the photometric signal-to-noise ratio.…”
Section: Simulation Of a Sample Of Lenses Seen By Romanmentioning
confidence: 99%